Exploring food shopping, consumption and waste habits in North Macedonia during the COVID-19 pandemic - Zvezda Bogevska; Sinisa Berjan; Hamid El Bilali; Mohammad Sadegh Allahyari; Adriana Radosavac; Margarita Davitkovska (Elsevier BV, 2022)
Household food waste (FW) has huge environmental and socio-economic impacts. During the COVID-19 pandemic, a survey was carried out in North Macedonia to explore perceptions and attitudes towards FW at the household level. A self-administered questionnaire was available online from 15th of May until June 30, 2020 and the sample size was 754. A very high percentage of the respondents (94.16%) expressed a high awareness of food waste and declared to worry about this issue trying to avoid food waste as much as possible. Moreover, the results showed that 41.38% of the respondents think to waste a low amount of food while 27.98% state not to throw almost anything. Meanwhile, 52.39% of the respondents believe that they do not throw away food that is still consumable. About 22.54% of them think to throw less than 250 g followed by those who think to throw between 250 and 500 g (18.04%). The survey showed that the most wasted food groups are cereals and bakery products, fruit, vegetables, and milk and dairy products. Concerning economic value, most of the respondents (53.18%) believe to spend less than 5 EUR on food wasted while 42.04% of them think to spend between 5 and 25 EUR. Regarding shopping behaviour during COVID-19, only about a half of the respondents (48.28%) stated to go shopping like they used to do. The respondents declared that they have bought during COVID-19 more vegetables (72.30%) and fruits (68.60%), which might imply that they are moving towards healthier diets. It seems that food wastage has increased during the COVID-19 for about a third of the respondents (34.70%). The survey showed that the COVID-19 pandemic affected food purchase, wastage and consumption behaviours in North Macedonia. Such a finding should inform future policies and initiatives relating to agriculture, food and health during the recovery period.
Keywords: food waste, food shopping, food consumption, COVID-19, coronavirus